Breaking into BIM: Performing static and dynamic security analysis with the aid of BIM - Porter, Stuart; Tan, Terence Peng Lian; Tan, Tele; West, Geoff (Elsevier BV, 2014)
The design and construction industry is moving towards Building Information Models (BIM) that provide all of the strengths of traditional 3D CAD with an added layer of data allowing new and powerful applications. We investigate the concept of using the data within BIM to better explore security design and considerations. We achieve this by first graphing the physical entities of BIM to capture their relational representation as nodes and links. This graph representation will facilitate the use of graph theory or agent-based simulation to assist in the analysis of the static and dynamic behaviour of the environment around the BIM. We also demonstrate an application of graphing by investigating the use of BIM to explore automated infrastructure security design and consideration via red-teaming. The intent is to make security analysis easier and a process that can be carried out during the design phase of a project, even by non-expert users.